2018
DOI: 10.1097/ico.0000000000001509
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea Assessed by Overnight Polysomnography in Patients With Keratoconus

Abstract: As measured by overnight home sleep apnea testing, OSA was 10 to 20 times more prevalent among patients with KCN than the rate reported for the general population. The rate lies between the prevalence estimated from sleep study data of self-reported diagnosis of OSA and the risk of developing OSA as determined by the Berlin Questionnaire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…We have shown that KC remains stable over 12 months in patients supplemented with Vit D. KC has been traditionally considered an isolated ocular disease, whereas recent evidence suggests that KC is, in fact, a manifestation of a systemic disorder. Indeed, it is known that 21% to 70% of KC patients present a concomitant systemic disease, such as atopy, 41 , 42 sleep apnea, 43 mitral valve prolapse, 44 , 45 hypothyroidism, 46 or Down syndrome. 47 , 48 Interestingly, many of these diseases are associated with Vit D insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that KC remains stable over 12 months in patients supplemented with Vit D. KC has been traditionally considered an isolated ocular disease, whereas recent evidence suggests that KC is, in fact, a manifestation of a systemic disorder. Indeed, it is known that 21% to 70% of KC patients present a concomitant systemic disease, such as atopy, 41 , 42 sleep apnea, 43 mitral valve prolapse, 44 , 45 hypothyroidism, 46 or Down syndrome. 47 , 48 Interestingly, many of these diseases are associated with Vit D insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The association between increasing NC and increased risk of developing obstructive sleep apnea has been well documented in the literature. [21][22][23] Additionally, OSA has been associated with increased risk of incident HF. [24] Additional research on potential mechanisms of the association between NC and HF is needed.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there is no clinical evidence of associated systemic diseases. There are, however, some exceptions; atopy [13], sleep apnea [14], mitral valve prolapse [15,16], hypothyroidism [17], and Down's syndrome [18,19] have been detected in a percentage of KC patients varying from 21% to 70%. It is interesting to note that many of these diseases cause metabolic [20][21][22] and/or nutritional [22,23] imbalance.…”
Section: Introductionmentioning
confidence: 99%